2017
DOI: 10.1515/ssa-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of various practices of the mitigation of N2O emissions from the arable soils of Poland

Abstract: Streszczenie: Celem pracy by³a ocena efektywnooeci i mo¿liwooeae wdro¿enia praktyk mitygacji emisji N 2 O w warunkach glebowoklimatyczno-agrotechnicznych Polski. Analizie poddano praktyki polegaj¹ce na: zmniejszeniu dawki azotu, doborze jego formy w nawozach i zastosowaniu inhibitorów biologicznych przemian zwi¹zków azotowych w glebie, regulacji odczynu gleby, kontroli i zmniejszeniu dawek nawozów naturalnych, zalesianiu gleb najs³abszych. Analiza dostêpnych danych wykaza³a, ¿e warunki sprzyjaj¹ce intensywnej … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A study by Syp et al (2016) showed that N 2 O emissions from cultivated soils in Poland varied within the range of 1.99-3.78 kg N 2 O ha/year. A reduction in these greenhouse gas emissions from agriculture can be achieved by: (i) large-scale implementation of precision farming; (ii) growing crops with a high carbon sequestration potential; (iii) organic fertilization; (iv) growing energy crops; (v) organic farming; (vi) afforestation of agricultural land (Sosulski et al 2017). The agronomic factors influencing N 2 O emission into the atmosphere include the method of soil cultivation, introduction of organic matter, and mineral fertilization (Ball et al 2014, Martins et al 2015, Pimentel et al 2015.…”
mentioning
confidence: 99%
“…A study by Syp et al (2016) showed that N 2 O emissions from cultivated soils in Poland varied within the range of 1.99-3.78 kg N 2 O ha/year. A reduction in these greenhouse gas emissions from agriculture can be achieved by: (i) large-scale implementation of precision farming; (ii) growing crops with a high carbon sequestration potential; (iii) organic fertilization; (iv) growing energy crops; (v) organic farming; (vi) afforestation of agricultural land (Sosulski et al 2017). The agronomic factors influencing N 2 O emission into the atmosphere include the method of soil cultivation, introduction of organic matter, and mineral fertilization (Ball et al 2014, Martins et al 2015, Pimentel et al 2015.…”
mentioning
confidence: 99%
“…In addition to changing dietary habits, it is also proposed to reduce GHG emissions by reducing emissions from nitrogen fertilizers through the reduction of their use, the use of inhibitors and ensuring an adequate soil pH [112]. Technological changes aimed at reducing the level of GHG emissions also include breeding progress.…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of all agricultural greenhouse gas emissions come from CH 4 emissions from enteric fermentation and N 2 O emissions from soil [9]. CH 4 is the third most important source of emissions from manure treatment, accounting for about 10%.…”
Section: Introductionmentioning
confidence: 99%